A Comparison of the Species Composition of Arrenurus Duges (Arrenuridae: Hydrachnidia: Acari) in Turkey and Some Countries in Palearctic Region - Orhan ERMAN; Başak ARSLAN; Pınar GÜLLE (Mehmet Akif Ersoy Üniversitesi Fen Bilimleri Enstitüsü, 2020)
This study aimed to determine the distributions, habitats and endemism rates of Arrenurus from Turkey. Similarity indices were determined between Turkey and some countries in the Palearctic Region. Sorensen and Jaccard similarity indices were used for the similarity comparisons. Both calculations show that Arrenurus fauna of Turkey has a high similarity with that of France, the Netherlands and Belgium, but the lowest similarity with Japan. It has also been reviewed the contributions made to the genus Arrenurus in Turkey. Additionaly, the female of Arrenurus dileri Boyacı and Özkan 2004 was misidentificated, it is determined Arrrenurus walkanoffi (Viets, 1926).